El deafo - Bell, Cece; Lasky, David (New York : Amulet Books, 2014)
That requires superpowers! In this graphic novel memoir, author/illustrator Cece Bell chronicles her hearing loss at a young age and her subsequent experiences with the Phonic Ear, a very powerful--and very awkward--hearing aid.
Keywords: Bell, Cece -- Comic books, strips, etc; Bell, Cece -- Childhood and youth -- Comic books, strips, etc; Deaf -- United States -- Biography -- Comic books, strips, etc; Authors, American -- Biography -- Comic books, strips, etc; Deaf children -- Comic books, strips, etc; Schools -- Comic books, strips, etc; Hearing aids for children -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Cartoonists -- Biography -- Comic books, strips, etc; Comic books, strips, etc; Graphic novels